Asymmetric strategy for enhanced performance of flexible electroadhesive clutch. Issue 2 (February 2023) - Li, Jun; Xiong, Ying; Ma, Kitming; Yang, Bao; Ma, Linlin; Tao, Xiaoming
Abstract: Flexible electroadhesive clutches with high shear stress and fast response working at low voltage are much desired in wearable electronics and robotic systems. Dielectric materials with opposite charge characteristics could maximize the clutch performance by taking advantages of the boosted electroadhesion between the two contact pads in an asymmetrically structured clutch. In this paper, asymmetrically structured electroadhesive clutches are proposed and reported for the first time. The asymmetric structured clutch exhibits a two-fold increment in the shear force but similar response time by simply reversing the electrode polarity. This work provides a new dimension to realize high-performance electroadhesive clutches based on an asymmetric strategy.